2016
DOI: 10.1177/2056305116664220
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Venting in the Social Web: Effects of Anonymity and Group Norms on Aggressive Language Use in Online Comments

Abstract: Scholars often blame the occurrence of aggressive behavior in online discussions on the anonymity of the Internet; however, even on today’s less anonymous platforms, such as social networking sites, users write plenty of aggressive comments, which can elicit a whole wave of negative remarks. Drawing on the social identity and deindividuation effects (SIDE) model, this research conducts a laboratory experiment with a 2 (anonymity vs. no anonymity) × 2 (aggressive norm vs. non-aggressive norm) between-subjects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 29 publications
(48 reference statements)
4
98
1
2
Order By: Relevance
“…Research has also revealed that witnessing homophobic bullying offline predicted the perpetration of homophobic bullying (Orue and Calvete 2018). Furthermore, Social Learning Theory proposes that observing deviant behaviors and/or perceiving that the peer group accepts such behaviors might relate to higher incidences of deviant behaviors among adolescents (Akers et al 1979;Rösner and Krämer 2016). Consistent with this perspective, Pratti (2012a) found that social and cognitive factors accounted for adolescents' homophobic aggression.…”
Section: Witnessing Homophobic Cyberbullyingmentioning
confidence: 99%
“…Research has also revealed that witnessing homophobic bullying offline predicted the perpetration of homophobic bullying (Orue and Calvete 2018). Furthermore, Social Learning Theory proposes that observing deviant behaviors and/or perceiving that the peer group accepts such behaviors might relate to higher incidences of deviant behaviors among adolescents (Akers et al 1979;Rösner and Krämer 2016). Consistent with this perspective, Pratti (2012a) found that social and cognitive factors accounted for adolescents' homophobic aggression.…”
Section: Witnessing Homophobic Cyberbullyingmentioning
confidence: 99%
“…Because of the growing popularity of leaving and reading comments online, these spaces for public discourse have become an important topic for communication research. Scholars have examined news comment sections to understand the impact of interactivity and other content features (Weber, 2014;Ziegele, Breiner, & Quiring, 2014), the quality of news comments (Coe et al, 2014;Rowe, 2015aRowe, , 2015bSantana, 2014), motivations for commenting (Springer, Engelmann, & Pfaffinger, 2015;Stroud et al, 2016), personal characteristics of news commenters (Wu & Atkin, 2017), and the influence of news comments on users' evaluation of news articles and social issues (Anderson, Brossard, Scheufele, Xenos, & Ladwig, 2014;Prochazka et al, 2016) and their future commenting behaviors (Rösner & Krämer, 2016). In addition, from the perspective of journalists, there have been a number of studies of how reporters and editors react to and negotiate the value of news comments (e.g., Loke, 2012;Nielsen, 2014;Robinson, 2010).…”
Section: Online News Commentingmentioning
confidence: 99%
“…Тем не менее граница социальной приемлемости, о которой говорилось выше, дает нам возможность думать о стигматизации жертв сексуального насилия и о том, что изнасилование менее социально приемлемо (а инцест приемлем еще в меньшей степени) -то есть что «внешняя» норма, табуирующая разговор о сексуальном насилии, здесь проявляется, отсекая часть опытов и историй. Возможно, если бы этот флешмоб проходил на площадке с большей степенью анонимности (или если рассмотреть истории, опубликованные при большей степени анонимности -под фейковыми аккаунтами), то мы увидели бы больше таких социально неприемлемых историй и меньше accounts, потому что групповая норма флешмоба не предполагает использование accounts (наоборот -проникновение конкурирующей нормы, доминирующего дискурса), а соответствие групповой норме в анонимной среде выше [Postmes, Spears 1998;Postmes et al, 2001], даже если эта норма предполагает поведение, которое в другом контексте расценивается как девиантное (например, агрессия [Rösner, Krämer, 2016]). Публикуя пост на онлайнплощадке с любой степенью анонимности, человек подчиняется групповой норме, существующей на этой площадке (либо подвергается санкциям) -но положение онлайн-площадки на континууме анонимности (или диапазон возможной степени анонимности для пользователя на этой площадке) может задавать определенную степень соответствия этой норме в поведении пользователей.…”
Section: данныеunclassified